Dynamics of ammonia consist in the rumen of calves - Замазій, А. А.; Камбур, М. Д.; Колечко, А. В. (Scientific Progress & Innovations, 2017)
The article presents the results of studies that prove that the dynamics of ammonia content in the rumen in calves over the autumn-winter and winter-spring period has changed. In the control subgroups of the first group born in the autumn-winter and winter-spring period, the contents of ammonia in the rumen were significantly different at the beginning of the studies. During the appearance of the ruminant process in the calves of the autumn-winter period of birth, the contents of ammonia in the rumen were 8,80±0,80 mg%, and in calves of the winter-spring period of birth, 3,41 % more. On average, the calves of the experimental subgroup of the first group of the autumn-winter period, the content of ammonia during the study period was 1,08, 1,07 and 1,13 less than the calves of the control subgroup.